Antigenic characterization of an Indian isolate of infectious bursal disease virus (IBDV-P/AD/81) with overseas monoclonal antibodies - DAS, S C; RAM, G C; VERMA, K C; KATARIA, J M (The Indian Journal of Animal Sciences, 2013)
The Indian isolate of infectious bursal disease virus, viz. IBDV-P/AD/81. when reacted with monoclonal antibodies (MoAb) P40/IV/B4 and P40/B1 (directed against 40 kd (VP2) polypeptide of chicken isolate Cu-I) showed maximum reactivity in ELISA and neutralization, and formed precipitin bands in AGPT indicating its antigenic similarity with exotic chicken isolate Cu-l. MoAb P32/E1 (directed against 32 kd (VP3) polypeptide of chicken isolate Cu-l), though highly reacted in ELISA but did not show any neutralization and was not precipitating. The virus did not react in ELISA. AGPT and neutralization with MoAb m/AK/T/41/A2 (directed against 41 kd (VP2) polypeptide of turkey isolate 23/82) indicating its antigenic dissimilarity within the exotic turkey isolate 23/82.